CLINICAL CHARACTERISTICS AND ¹⁸FDG PET/CT IMAGING IN DIFFERENTATEDTHYROID CARCINOMA PATIENTS WITH NEGATIVE ¹³¹I WHOLE-BODY SCAN AND ELEVATED SERUM THYROGLOBULIN - LE , NGOC HA; LE , MANH HA; LE , DUY HUNG; NGUYEN , THANH HUONG (Nuclear Science and Technology, 2012)
Differentiated thyroid carcinoma (DTC) represents about 1 – 1.5% of all malignant tumors. Post-surgical total thyroidectomy and 131 I therapy patients have a 10-year survival rate of 85 – 90%. However, DTC patients have a less favorable prognosis if radioiodine - negative tumor tissues, especially in distant metastases, is present. Several studies showed that 18FDG PET/CT can improve the diagnostic work-up of these patients with negative radioiodine scintigraphy but metastatic spread associated with an increase of serum thyroglobulin.